Pijat pada Ibu Postpartum dengan Onset Laktasi - Riana Andam Dewi; Cia Aprilianti (Jurnal Kesehatan, 2018)
Massage can be used as a non-pharmacological therapy to stimulate oxytocin to speed up the of onset lactation. If the onset of lactation happens quickly, then it should be breastfed as a baby's first nutrition life. This type of massage is a massage include massage lactation and oxytocin. The purpose of this study was to determine the difference in onset of lactation in postpartum mothers based on the type of massage given. The study design using Quasy Experiment, with the draft Non-Equivalent Control Group Design. The sampling technique was purposive sampling. The total sample was 40 mothers postpartum in Praktik Independent Midwives Ni Made Nuriasih and Praktik Independent Midwives Winanti in the city of Palangkaraya, then divided into 2 groups, 20 mothers postpartum performed postpartum maternal lactation massage and 20 mothers do massage oxytocin. A statistical test was using Independent T-test. The statistical analysis showed that mothers who do massage postpartum lactation had an average the onset of 35.05 hours of lactation. While the postpartum mother performed the oxytocin massage, there was a slower onset of lactation with an average of 49.14 hours. There was a significant difference in the average onset of lactation in postpartum women who performed lactation massage with postpartum mothers who performed oxytocin massage, where the onset of lactation in postpartum mothers performed lactation massage faster than postpartum mothers who performed oxytocin massage (p-value of 0.002). So, massage on postpartum mothers, especially lactation massage can be used as additional services to mothers after childbirth to facilitate the production and expenditure of breast milk, to support exclusive breastfeeding.